Composite proton exchange membrane and preparation method thereof - OU YING; QIN CAIQIN; WANG GUANGJIN; WANG JIE; LIU HAI; GONG CHUNLI; ZHENG GENWEN; WEN SHENG (2017)
The invention provides a composite proton exchange membrane and a preparation method thereof, and relates to the field of fuel cells. The preparation method of the composite proton exchange membrane comprises the steps of preparing carbon nanotubes coated with sulfurated zirconia into dispersion liquid, mixing the dispersion liquid with an acid solution of chitosan, and drying to obtain a dry film; carrying out alkaline cleaning on the dry film, and then washing until the dry film is neutral; obtaining the composite proton exchange membrane under the action of a cross-linking agent. The prepared composite proton exchange membrane has good water absorption, proton conductivity, mechanical properties and thermal stability, thus having a wide application prospect in polymer-based fuel cells. 本发明提供种复合质子交换膜及其制备方法，涉及燃料电池领域。复合质子交换膜的制备方法，包括：将硫化氧化锆包覆的碳纳米管制成分散液，将分散液与壳聚糖的酸溶液混合和烘干得到干膜，对干膜进行碱洗后水洗至中性，在交联剂的作用下得到复合质子交换膜。制得的复合质子交换膜，具有良好的吸水率、质子传导率、机械性能和热稳定性，在聚合物基燃料电池中有广阔的应用前景。